THE RELATIONSHIP BETWEEN READING INTEREST AND MOTIVATION TO LEARN IN IMPROVING ACADEMIC ACHIEVEMENT - Donald Samuel Slamet Santosa; Ramadhan Panji Baskoro (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the relationship between reading interest and Motivation to Learn on the Academic Achievement of third-grade students at SDN Jatibaru 02, Cikarang. A quantitative method with a descriptive associative approach was employed. The population and sample comprised all 47 third-grade students. Data were collected using a Likert-scale questionnaire to measure reading interest and Motivation to Learn, along with academic records to assess Academic Achievement. Instrument validity was tested using Pearson correlation, and reliability was assessed with Cronbach’s alpha. Classical assumption tests included normality, multicollinearity, heteroscedasticity, and autocorrelation. Data analysis was conducted using multiple linear regression. The results reveal that, partially, reading interest does not have a significant effect on Academic Achievement, whereas Motivation to Learn exerts a positive and significant influence. Simultaneously, reading interest and Motivation to Learn together explain approximately 44.5% of the variance in students’ Academic Achievement, with the remaining 55.5% attributed to factors outside the model. These findings underscore the critical role of Motivation to Learn as the primary driver of academic success and highlight the need to enhance literacy programs integrated with motivational strategies to more effectively support improvements in academic performance.